Pelatihan Kebersyukuran untuk Menurunkan Kecemasan Menghadapi Ujian Nasional pada Siswa SMA - Hamid Mukhlis; Koentjoro Koentjoro (Faculty of Psychology, Universitas Gadjah Mada, 2015)
Standardized state Exam (Ujian Nasional/UN) is one of the root causes of anxiety instudents. The results of a preliminary study in SMAN Y Yogyakarta known 29% students of class XII having anxiety in dealing with the UN. Test anxiety will affect the performance of students for the examination. This study develops Kebersyukuran training as an alternative to solving anxiety permasalahans facing the UN in Class XII. The design used is untreated Control Group Design With Pretest And Posttest Sample. Quantitative data analysis is done through a mixed ANOVA statistical test to determine the effects of training kebersyukuranthe experimental group and the control group between before and after training. The resultsof the study are kebersyukuran training can reduce anxiety dealing with the UN on highschool students.